2021
DOI: 10.1155/2021/5575545
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Properties of Valsartan: Do They Result from the Antiglycooxidant Activity? Literature Review and In Vitro Study

Abstract: Valsartan belongs to angiotensin II type 1 (AT1) receptor blockers (ARB) used in cardiovascular diseases like heart failure and hypertension. Except for its AT1-antagonism, another mechanism of drug action has been suggested in recent research. One of the supposed actions refers to the positive impact on redox balance and reducing protein glycation. Our study is aimed at assessing the antiglycooxidant properties of valsartan in an in vitro model of oxidized bovine serum albumin (BSA). Glucose, fructose, ribose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 102 publications
3
18
0
Order By: Relevance
“…The study performed most recently with another nephroprotective class of drugs-angiotensin II receptor blockers (ARB)-demonstrated their antiglycooxidant activity. These findings support the need for future studies in this area with the use of SGLT2i [63]. Given the fact that some literature reports suggest SGLT2i interact with AGEs during their formation, the next step in future studies could address this matter further [64][65][66].…”
Section: Discussionsupporting
confidence: 72%
“…The study performed most recently with another nephroprotective class of drugs-angiotensin II receptor blockers (ARB)-demonstrated their antiglycooxidant activity. These findings support the need for future studies in this area with the use of SGLT2i [63]. Given the fact that some literature reports suggest SGLT2i interact with AGEs during their formation, the next step in future studies could address this matter further [64][65][66].…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, the TAC method measures only part of the antioxidant capacity, i.e. nonenzymatic activity [23,42]. In our study we observed diminished plasma TAC in patients with pheochromocytoma.…”
Section: Discussionsupporting
confidence: 44%
“…In a type 2 diabetic nephropathy rat model, two anti-hypertensive drugs of different mechanisms of action, i.e., olmesartan and hydralazine, were found to inhibit in vivo formation of protein pentosidine in the kidney and to improve renal damage (Nangaku et al 2003). Analogous results were observed for various AGEs in vivo and in vitro for valsartan (Mil et al 2021; see also Prasad and Mishra 2017).…”
Section: Discussionmentioning
confidence: 74%